Efficacy of endoscopic mucosal resections for the management of small gastric adenomas with low-grade dysplasia. (September 2015) - Park, Sung Min; Kim, Joon Sung; Ji, Jeong-Seon; Choi, Hwang; Lee, Bo-In; Kim, Byung-Wook
Abstract Objective. Gastric adenoma with low-grade dysplasia (LGD) can progress to gastric cancer; however, the optimal therapeutic modality for LGD has not been established. The aim of this study was to assess the efficacy, safety of and local recurrence following endoscopic mucosal resection (EMR) for LGD. Specifically, we compared EMR with circumferential precutting (EMR-P) and EMR using a dual-channel endoscope (EMR-D) for the treatment of LGD ≤2 cm. Materials and methods: A total of 158 lesions from 147 patients with LGD treated by EMR were retrospectively analyzed. The en bloc resection rate, complete resection rate, procedure time, complication rate and local recurrence rate were compared between EMR-P and EMR-D. Results. The en bloc resection and complete resection rates of EMR were 91.1% and 90.5%, respectively. The bleeding and perforation rates were 1.3% and 1.3%, respectively. The local recurrence rate following EMR was 2.2%. The en bloc resection and complete resection rates did not differ between EMR-P and EMR-D (88.2% vs. 92.5%, p = not significant (NS); and 90.2% vs. 90.7%, p = NS, respectively). The procedure time was significantly longer for EMR-P compared with EMR-D (16 (5–141) vs. 7 (2–48) min, p < 0.001), and the complication rate was significantly higher for EMR-P (7.8% vs. 0.0%, p = 0.010). Local recurrence was not found in EMR-P, whereas the recurrence rate was 3.2% in EMR-D. Conclusion. EMR is an effective method for the treatment of LGD ≤2 cm. Compared with EMR-P, EMR-D appears to be the more effective, technically simple and safer method.